The impact of informatization on agri-income of China's rural farmers: ways for digital farming - Xiaoyan, Du; Jiangnan, Zhang; Xuelian, Gao; Ali, Majid (Frontiers in Sustainable Food Systems, 2024)
Informatization, a vital element in economic development, plays a pivotal role in shaping rural areas by promoting efficient resource allocation and fostering the prosperity of high-income rural farmers. This research delves into the intricate relationship between informatization and the enhancement of farmers' income, revealing a variety of perspectives on the matter. The research explores three distinct angles that highlight the complexities of the relationship between informatization and the growth of income in rural areas. Through rigorous analysis, the study aims to provide insights into the interplay between informatization and farmers' income growth. It identifies challenges and opportunities in the process of rural digitalization, such as the incomplete industrial chain of agricultural digitalization and the need for enhanced agricultural market information platforms. The study also underscores the importance of increasing farmers' digital literacy as a means to broaden income growth avenues. In doing so, the research strives to contribute to a more balanced and equitable rural society in China. This investigation employs various research methodologies, including panel analysis and threshold effect analysis, to explore the multifaceted relationships between informatization and farmers' income growth. The findings of this study provide valuable insights for policymakers and stakeholders involved in the ongoing development of rural areas and in ensuring the equitable distribution of wealth in China.